A Ten Year Study of Management of Ischemic Heart Disease in a Tertiary Hospital in South West Nigeria (Global Journal of Medical Research, 2013)
The Pharmacotherapy of drugs used in the management of ischemic heart disease at the University College Hospital (UCH) in Ibadan between June 1998 and May 2007, was studied retrospectively. The objective was to assess the rational use of the prescribed drugs and to determine the tolerability and benefits of using nitrates, beta-blockers, calcium channel blockers and acetylsalicylic acid (aspirin). A total of 52 case files of patients with ischemic heart disease were randomly selected from the central medical record department and used for the study. Information extracted includes demographic data, the prescribed drugs and side effects.
Keywords: ischemic heart disease; pharmacotherapy; management; prescriptions; patients